1990
DOI: 10.1161/01.cir.82.1.289
|View full text |Cite
|
Sign up to set email alerts
|

Block of delayed rectifier potassium current, IK, by flecainide and E-4031 in cat ventricular myocytes.

Abstract: (Circulation 1990;82:289-293) T he delayed rectifier outward potassium current, IK, is believed to play a major role in repolarizing the cardiac action potential.' Selective block of IK has been shown to underlie the uniform increase in action potential duration (APD) produced by the class III antiarrhythmic agents,2-5 whereas many class I antiarrhythmic agents, such as quinidine and cibenzoline, possess K' channel blocking properties that contribute to their antiarrhythmic drug action as well as to their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(80 citation statements)
references
References 20 publications
5
75
0
Order By: Relevance
“…A major advantage conferred by such a preparation over recordings from native cardiomyocytes is the lack of overlapping and potentially contaminating currents; this facilitates the accurate characterization of drug actions. For example, whilst I K tails from feline myocytes were reported to be sensitive to both E-4031 and FLEC (Follmer & Colatsky, 1990), time-dependent outward current during applied depolarizations was only sensitive to blockade by FLEC in some preparations (Follmer et al, 1992). In subsequent experiments on guinea-pig myocytes (Wang et al, 1996), the presence of overlapping I Ks precluded detailed analysis of the FLEC e ect on I Kr .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major advantage conferred by such a preparation over recordings from native cardiomyocytes is the lack of overlapping and potentially contaminating currents; this facilitates the accurate characterization of drug actions. For example, whilst I K tails from feline myocytes were reported to be sensitive to both E-4031 and FLEC (Follmer & Colatsky, 1990), time-dependent outward current during applied depolarizations was only sensitive to blockade by FLEC in some preparations (Follmer et al, 1992). In subsequent experiments on guinea-pig myocytes (Wang et al, 1996), the presence of overlapping I Ks precluded detailed analysis of the FLEC e ect on I Kr .…”
Section: Discussionmentioning
confidence: 99%
“…Flecainide is e ective against a variety of supraventricular arrhythmias (Falk & Fogel, 1994) and exhibits a low incidence of QT interval prolongation and torsade de pointes (Lui et al, 1982;Wickers et al, 1988;Sarubbi et al, 1996). Experiments performed on feline ventricular myocytes have shown blockade by¯ecainide of delayed recti®er tail currents consistent with identity as I Kr (Follmer & Colatsky, 1990;Follmer et al, 1992). Limited data from guinea-pig ventricular myocytes also suggest that ecainide can inhibit I Kr (Wang et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is wellknown that many antiarrhythmic drugs selectively or nonselectively inhibit I Kr . Flecainide and aprindine were shown to inhibit I Kr (Follmer & Colatsky, 1990;OhmotoSekine et al, 1999) whereas quinidine, cibenzoline and bepridil were reported to block both I Kr and I Ks (Balser et al, 1991;Wang et al, 1996;. In terms of class III antiarrhythmic drugs, sotalol, E-4031 and dofetilide selectively inhibited I Kr (Sanguinetti & Jurkiewicz, 1990;Jurkiewicz & Sanguinetti, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…On repolarization each current trace is followed by a slowly decaying current tail. This current has been identified as the delayed rectifying current (IK) (Follmer & Colatsky, 1990;Furukawa et al, 1992). Berberine decreased the current activated during the depolarizing pulse and the subsequent tail current.…”
Section: Single Cell Isolationmentioning
confidence: 99%